Distance Education and Cyberseniors: a focus on teaching strategies - Leticia Rocha Machado; Patrícia Alejandra Behar (Universidade Federal do Rio Grande do Sul, 2014)
This paper discusses the construction of pedagogical strategies in Distance Learning (DL) in order to include cyberseniors in virtual courses. The study was conducted through a qualitative and quantitative approach. It comprised seven stages of development. The data was collected by participant observation, interviews, questionnaires, and technological productions of the participants. The results showed the need to deepen aspects such as resilience and reminiscence with older audiences. With a larger gerontological contribution, it will be possible to provide actions covering the full educational potential of DL with the elderly.